Nietzsche in Hollywood : images of the Übermensch in early American cinema - Rukgaber, Matthew (SUNY series, horizons of cinema., 2022)
"Argues that Nietzsche's idea of the Übermensch was a central concern of filmmakers in the 1920s and 1930s"--